Foundations of financial markets and institutions - Fabozzi, Frank J. (Prentice-Hall International, 1998)
Foundations of Financial Markets and Institutions, offers a comprehensive exploration of the revolutionary developments occurring in the world's financial markets and institutions –i.e., innovation, globalization, and deregulation–with a focus on the actual practices of financial institutions, investors, and financial instruments.